Symmetry restored in dibosons at the LHC? - Brehmer, Johann; Hewett, JoAnne; Kopp, Joachim; Rizzo, Thomas; Tattersall, Jamie (Journal of high energy physics, 2015)
A number of LHC resonance search channels display an excess in the invariant mass region of 1.8-2.0 TeV. Among them is a 3.4σ excess in the fully hadronic decay of a pair of Standard Model electroweak gauge bosons, in addition to potential signals in the HW anddijetfinalstates. Weperformamodel-independentcross-sectionfittotheresults of all ATLAS and CMS searches sensitive to these final states. We then interpret these results in the context of the Left-Right Symmetric Model, based on the extended gauge group SU(2)L× SU(2)R× U(1)′, and show that a heavy right-handed gauge boson WRcan naturally explain the current measurements with just a single coupling gR∼ 0.4. In addition, we discuss a possible connection to dark matter.
Gesehen am 28.05.2015